Combination of Phytoactives in the Diet of Lactating Jersey Cows: Effects on Productive Efficiency, Milk Composition and Quality, Ruminal Environment, and Animal Health - de Vitt M.G.* (2024)
© 2024 by the authors.This study’s objective was to evaluate whether adding a combination of phytoactive (microencapsulated essential oils, minerals, turmeric extract, tannin, prebiotic, and probiotic) to the feed of lactating Jersey cows positively affects the production, composition, and quality of milk, rumen environment, and animal health. Fourteen Jersey cows were divided into two groups (control and phytogenic) for an experiment with two lactation phases of 45 days each (early lactation and mid-lactation). During the experiment, milk production was higher at various times in cows that consumed phytoactive, and these animals had the best feed efficiency. In mid-lactation, phytoactive intake increased nutrient digestibility. The number of lymphocytes in the blood is reduced when cows consume phytoactive substances. Globulin levels increased in these cows fed with the additive, which may be related to a higher concentration of immunoglobulins, especially IgA. Cows fed phytoactives had lower ceruloplasmin and haptoglobin concentrations. Lower serum lipid peroxidation, associated with greater glutathione S-transferase activity, is a good health indicator in cows that consume phytoactive substances. The higher concentration of volatile fatty acids was due to the higher proportion of acetic acid in the ruminal fluid combined with lower butyric acid. Somatic cell counts in milk were lower in cows that consumed phytoactives during mid-lactation, as well as the effect of the treatment on Streptococcus spp. (lower in cows that consumed the additive). We conclude that consuming the additive benefits cows’ health modulates rumen fermentation and nutrient digestibility, and positively affects milk production and quality.